Stimuli‐responsive hydrogels: Fabrication and biomedical applications. Issue 2 (27th August 2021) - Li, Ziyuan; Zhou, Yanzi; Li, Tianyue; Zhang, Junji; Tian, He
Abstract: Due to their similarity to some bio‐architectures, for example, extracellular matrix, hydrogels are considered as bio‐inspired networks with bio‐mimetic and bio‐functional properties. With natural cytocompatibility and biocompatibility, hydrogels nowadays are more and more involved in various bio‐applications including shape morphing, artificial muscles, soft robotics, regenerative medicine, and so on. As an important subclass, stimuli‐responsive hydrogels have been attracting interest within decades. In response to single or multi‐triggers in biological microenvironment, stimuli‐responsive hydrogels can undergo phase transition, stiffness change, or biochemical properties activation, which make them intriguing biomaterials with broad applications including sensing, drug delivery, tissue engineering, and wound healing. This review presents typical synthetic and natural gelators comprising small molecules and polymers as building blocks of functional architectures. The fabrication strategies of hydrogels varied from supramolecular assembly to dynamic covalent binding are detailed. Various exogenous or endogenous, physical or chemical, and synthetic or natural stimuli together with response mechanism, design principle are demonstrated. Through recent examples from different perspectives, such as bionic devices, wound dressing, and cargo carrier, the benefits and opportunities of stimuli‐responsive hydrogels for biological applications are highlighted. Finally, the current challenges and future prospects in view of translation from fundamental researches to clinical application are briefly discussed. Abstract : In this review, the authors aim to provide guidelines for researchers to design stimuli‐responsive hydrogels of their own interest. Different kinds of construction mode including supramolecular assembly, radical polymerization, chemical reaction and so on are introduced. Different hydrogels response to contact and non‐contact, synthetic and natural, and endogenous and exogenous signal are discussed. Various applications developed and will be developed in the future are evaluated, especially in the field of tissue engineering and regeneration medicine, which are still at its primary stage and in an urgent need of development. The growing of stimuli‐responsive hydrogels is expected to contribute to this field and provide promising perspectives.